KARAKTERISTIK PENDERITA DEMAM TIFOID YANG DI RAWAT INAP DI RUMAH SAKIT UMUM DAERAH Dr. RM. DJOELHAM KOTA BINJAI TAHUN 2016 - IKBAL Andrian MALAU; Rahayu Lubis; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Typhoid fever is a systemic infection caused by Bacteria Salmonella typhi, transmitted through the consumption of contaminated food/water. In 2015, Sumatera Utara Province is in the 28order out of 34 provinces with the success percentage of the Total Environmental Based SanitationProgram/STBM 8.49%. InDr. RM. DjoelhamHospital, typhoid fever is 1 of10 largest diseases of inpatient with the total of patients 108 people in 2016. This study aims to determine the characteristics of patients with typhoid feverhospitalized at Dr. RM. Djoelham Hospital of Binjai City in 2016. This research is descriptive with case seriesdesign, Population of this research is all data of inpatient typhoid fever which are 108 in total. The research sample use the whole population. Statistical analysis use Chi-Square test, Mann-Whitney test, Kruskal-Wallis test, and Exact Fisher test. The higest proportion of people with typhoid fever based on sociodemography is in 12-25 years old group (38.9%), female (56.5%), Java (70.4%), Islam (81,4%), students (55.5%), unmarried (74.1%), in Binjai City (99.1%),being treat directly/no referral (32.4%), fever (16.7%), average length of stay 2.88 days (3 days), recurrent typhoid (6 persons), JKN (86.1%), clinical recovery (54.6%). The Chi-Square test, show no significant difference betweenthe condition when being out of hospital based on clinical symptoms (p=0,822). The Mann-Whitney test, show significant difference between the average length of stay based on the cost source (p=0.011). Kruskal-Wallis test,show no significant difference between the length of stay based on the condition when being out of the hospital (p=0.176). The Exact Fisher test, show no significant proportion difference between the cost source based on the condition whe being out of hospital (p=0.329). Recommendedto doctors, nurses, midwives, and other health workers to encourage patients with typhoid fever to complete treatment so that there will be no recurrent tifoid or Carrier. Keywords :      Patients with Typhoid Fever, Characteristic, Dr. RM. Djoelham Hospital